Exploration of Life Skills of Teacher Prospective Students: What is it and how is the situation - Kiki Fatmawati (Tarbawi: Jurnal Keilmuan Manajemen Pendidikan, 2022)
This study aims to explore what life skills are possessed by prospective teacher students and what the conditions of these life skills are. The research method uses qualitative research with the type of descriptive research. Data were collected utilizing interviews, observations, and documentation related to the life skills of prospective teacher students. The research was conducted on student-teacher candidates in Jambi. The results showed prospective teacher students possessed the dimensions of life skills: self-awareness, personal skills, rational thinking, social skills, academic skills, and vocational skills. The state of life skills possessed by prospective teacher students differs from each dimension of life skills. The condition of his life skills is already very good, good, quite good, and not good. This finding concludes that there is a potential for the development of life skills for prospective teacher students so that they can bring up plans for developing life skills for prospective teacher students. Life skills are essential for students because they enable them to change knowledge, attitudes, and values ​​into actual abilities.